"A new and modern golden age of Jewish culture": shaping the cultural politics of transnational Jewish antifascism. Issue 3 (3rd July 2018) - Kaiser, Max
ABSTRACT: The Holocaust and a worldwide Jewish enthusiasm and support for the Red Army's defeat of the German Army on the Eastern Front led to a greater sense of international Jewish consciousness and solidarity often tied to an antifascist politics. Utilizing a transnational lens, I explore how Jewish antifascists of the immediate post-war period proffered a novel cultural politics as a means of addressing ongoing international issues of post-Holocaust Jewish survival in a dangerous and politically uncertain modernity. I examine three Jewish left magazines of the late 1940s that were involved in a loose international antifascist progressive Jewish network and ideological framework. These magazines Jewish Life (USA), New Life (UK) and Unity (Australia) represented similar antifascist politics and cultural outlooks in the USA, Britain and Australia, respectively. They have received little sustained scholarly attention previously. I analyse their vision of diverse multilingual Jewish cultures which were to be promoted and developed in any country where Jews lived and in whatever language they spoke. Their cultural vision represented antifascist values against bourgeois or nationalist Jewish culture and broadly reflected a pro-Soviet, progressive and Jewish internationalist, Popular Front politics and worldview.